Correlation of Hematological Parameters on Maternal and Pediatric Leprosy ImmunityRatio: A Study in Endemic Areas in East Java, Indonesia - Muhammad Yulianto Listiawan; Flora Ramona Sigit Prakoeswa; Anang Endaryanto; Cita Rosita Sigit Prakoeswa (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Leprosy is chronic infectious disease caused by Mycobacterium leprae. Endemic areas stillexisted with stable number of new cases including new cases of pediatric leprosy and female leprosy cases.Close contact and women’s role in household increase the risk of transmission of leprosy to their children.Population lived in endemic areas are prone to contract leprosy due to dysregulation of immune system. Thisstudy aims to analyze correlation of hematological parameters and immunity ration in maternal and pediatricleprosy in endemic areas.Methods: This is a cross-sectional study in endemic areas in Tuban Regency, East Java Province,Indonesia. The blood sample was taken from the subjects and underwent complete hematological parametertest (hemoglobin, red blood cells, white blood cells, platelets, hematocrit) and measurement of T cellsactivityratio(Th1/Th2 ratio and Th17/Treg ratio) by ELISA. Correlation test was done between blood testresultsand the immunity ratio of maternal and pediatric leprosy in endemic areas.Results: 33 pairs of maternal and pediatric leprosy cases were analyzed. This study found correlationbetween RBC (p value= 0.029) and HCT (p value= 0.038) with Th17/Treg ratio in children population. Nosignificant results observed in mothers population.Conclusion: The result of this study shows that hematological paramaters (HB and HCT) related to theTh17/Treg ratio and could play roles in the incidence of dysregulation of immune system in children leprosy.